2020
DOI: 10.2478/bjmg-2020-0030
|View full text |Cite
|
Sign up to set email alerts
|

Influence of potential gene polymorphisms on propofol dosage regimen in patients undergoing abdominal hysterectomy

Abstract: Propofol (2,6-diisopropylphenol) is the most common intravenous anesthetic used in modern medicine. It is postulated that individual differences in genetic factors [polymorphism of single nucleotide polymorphisms (SNPs)] in the genes encoding metabolic enzymes, molecular targets and molecular binding sites of propofol can be responsible for susceptibility to propofol effects. The aim of our study was to investigate the influence of the cytochrome P450 2B6 isozyme CYP2B6 (rs3745274), γ-aminobutyric acid type A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…According to the findings of Ivanov et al ( 48 ) the ABCB1 (c.3435C > T) variation has no effect on clinical parameters in propofol patients. Although there is limited information on the impact of this variant on propofol therapy, their findings are consistent with those of Zakerska-Banaszak et al ( 49 ), who found no statistically significant differences between propofol therapeutic effects and ABCB1 gene variants.…”
Section: Pharmacokinetics Of Propofolmentioning
confidence: 96%
See 1 more Smart Citation
“…According to the findings of Ivanov et al ( 48 ) the ABCB1 (c.3435C > T) variation has no effect on clinical parameters in propofol patients. Although there is limited information on the impact of this variant on propofol therapy, their findings are consistent with those of Zakerska-Banaszak et al ( 49 ), who found no statistically significant differences between propofol therapeutic effects and ABCB1 gene variants.…”
Section: Pharmacokinetics Of Propofolmentioning
confidence: 96%
“…Although it appeared that genetic variants in the CYP2B6 and GABAA(ε) genes might explain for some of this variation in vivo , the genetic variants studied did not account for the majority of it. Ivanov et al ( 48 ) found differences between the given propofol doses in patients with different genotype for the polymorphism studied i.e., in GABRA1 (c.1059 + 15G > A) carriers the initial, additional, and total dose of propofol decreased with age ( p > 0.05). GABRA2 rs35496835, GABRB1 rs1372496, GABRG2 rs11135176, GABRG2 rs209358, GAD1 rs3791878, SLC1A3 rs1049522, and gender were all revealed to be significant predictors of loss of consciousness latency following propofol administration ( 58 ).…”
Section: Pharmacodynamics Of Propofol – Mechanism Of Actionmentioning
confidence: 99%